Estrogen receptor subtype mediated anti-inflammation and vasorelaxation via genomic and nongenomic actions in septic mice - Zhang, Luyun; Wan, Hanxing; Zhang, Mengting; Lu, Wei; Xu, Feng; Dong, Hui (Frontiers in Endocrinology, 2023)
Aim: Sepsis is a life-threatening disease with high mortality worldwide. Septic females have lower severity and mortality than the males, suggesting estrogen exerts a protective action, but nothing is known about the role of vascular endothelial estrogen receptor subtypes in this process. In the present study, we aimed to study the estrogen receptors on mesenteric arterioles in normal and sepsis mice and to elucidate the underlying mechanisms. Methods: Sepsis was induced in mice by intraperitoneal injection of LPS. The changes in the expression and release of the serum and cell supernatant proinflammatory cytokines, including TNF-α, IL-1β and IL-6, were measured by qPCR and ELISA, and the functions of multiple organs were analyzed. The functional activities of mouse mesenteric arterioles were determined by a Mulvany-style wire myograph. The expression of phospholipase C (PLC) and inositol 1,4,5-trisphosphate receptor (IP3R) in endothelial cells were examined by Western blot and their functions were characterized by cell Ca2+ imaging. Results: Septic female mice had higher survival rate than the male mice, and pretreatment with E2 for 5 days significantly improved the survival rate and inhibited proinflammatory cytokines in septic male mice. E2 ameliorated pulmonary, intestinal, hepatic and renal multiple organ injuries in septic male mice; and ER subtypes inhibited proinflammatory cytokines in endothelial cells via PLC/IP3R/Ca2+ pathway. E2/ER subtypes immediately induced endothelial-derived hyperpolarization (EDH)-mediated vasorelaxation via PLC/IP3R/Ca2+ pathway, which was more impaired in septic male mice. E2/ER subtypes could rescue the impaired acetylcholine (ACh)-induced EDH-mediated vasorelaxation in septic male mice. Conclusions: E2 through ER subtypes mediates anti-inflammation and vasorelaxation via genomic and nongenomic actions in sepsis. Mechanistically, activation of endothelial ER subtypes reduces proinflammatory cytokines and induces EDH-mediated vasorelaxation via PLC/IP3R/Ca2+ pathway, leading to amelioration of sepsis-induced organ injury and survival rate.